Author Correction: Remote sensing quantifies widespread abundance of permafrost region disturbances across the Arctic and Subarctic - I. Nitze (Nature Portfolio, 2019)
The original version of this Article contained an error in the author affiliations. Affiliation 5 incorrectly read ‘Tyumen State Oil and Gas University, Tyumen, Tyument. Oblast, Russian Federation, 625000’.This has now been corrected in both the PDF and HTML versions of the Article.